Verbal expressions describing itch quality in atopic dermatitis and urticaria: an online questionnaire survey in Japan - Yukihiro Ohya; Toshiya Ebata; Yusei Ohshima; Tsugunobu Andoh; Mitsutoshi Tominaga; Yoko Kataoka; Yoshinori Fukui; Nobuyuki Ebihara; Shunji Hasegawa; Shigetoshi Kobayashi; Yutaka Morisawa; Norihiro Inoue; et al. (Frontiers Media S.A., 2024)
Background: The nature of itch sensation varies depending upon the patient and the disease. However, few studies have focused on verbal expressions describing itch of atopic dermatitis (AD) in quality.Objectives: To investigate itch quality in patients with AD compared with that of urticaria.Methods: We conducted an online questionnaire survey describing itch experiences in June 2021. Participants were Japanese patients who had visited hospitals for their consultations and treatments of AD or urticaria in the last 6 months, and 295 and 290 responses, respectively, to questions using 12 terms describing itch quality were analyzed.Results: The most suitable expression describing intense itch that patients could not help scratching differed between the diseases, where most AD patients selected "muzumuzu" (a mimetic word for creepy-crawly itch) (27%) or "painful itch" (20%), and most urticaria patients selected "muzumuzu" (24%) or "itch like mosquito bites" (22%). The most suitable expressions describing itch that would make patients happiest if improved was "painful itch" (27%) in AD patients, significantly higher than urticaria patients (19%). More AD patients (55%) responded that they sometimes felt itch even after the skin symptoms had subsided than urticaria patients (41%). The most suitable expression of remnant itch selected was "muzumuzu" for AD (58/161 patients, 36%) and urticaria (29/120 patients, 24%).Conclusion: The quality of itch sensations can be classified not only between diseases but also during the clinical course of each disease. Significant expressions that patients with AD use to describe itch sensations could promote more appropriate treatment for itch.